Infrared Spectroscopy - Life and Biomedical Sciences - Theophile Theophanides (IntechOpen, 2012)
This informative and state-of-the art book on Infrared Spectroscopy in Life sciences designed for researchers, academics as well as for those working in industry, agriculture and in pharmaceutical companies features 20 chapters of applications of MIRS and NIRS in brain activity and clinical research. It shows excellent FT-IR spectra of breast tissues, atheromatic plaques, human bones and projects assessment of haemodynamic activation in the cerebral cortex, brain oxygenation studies and many interesting insights from a medical perspective.
English
Keywords: Medicine; Diagnostics; Radiology Diagnosis; Health Sciences